Architecture students' attitudes toward emergency distance education and elements affecting their success in design studios: a sample from Turkey - Ekici, Betul Bektas; Akyildiz, Nihal Arda; Karabatak, Songul; Alanoglu, Muslim (Springer, 2024)
The COVID-19 pandemic has caused significant changes in almost every field globally and has also caused significant revisions in the education process of many disciplines, including architecture. The transition of the programs in architecture schools worldwide to distance education in 2020 has created an extraordinary experience of designing lectures for distance education apart from traditional methods. The current study examined the attitudes of students, who are thought to be most affected by this pandemic process, toward distance education in terms of the usefulness of and preference for distance education, the feeling of lack of social presence, and the preference for face-to-face education. This study also sought the factors affecting the success of students in design studios. The opinions of 970 students studying design at 20 universities in Turkey were sought. This mixed method study revealed that, together with the pandemic, distance education closely affected student success, especially in faculties where design courses are given. The attitudes of male students studying architecture are significantly more positive toward distance education compared to those of female students. The results illustrated that students with adequate Internet access also have better views on the usefulness of distance education compared to those with insufficient internet access. As the students' grade level in the faculty of architecture increased, their attitudes toward distance education changed positively. The overall results reveal that traditional education promotes student creativity and design capacity significantly in all departments associated with design and architecture. The findings of the present study underline the need for revisions in educational institutions with design formation, including schools of architecture, in terms of teaching methods for design lectures, thereby increasing and improving the quality of education.
Keywords: Design studio; Design lecture; Emergency distance education; Student attitudes